Synthesis and optimization of dopamine hydrochloride functionalized palygorskite and their application in protective coatings on water saturated surface of concrete. Issue 32 (5th April 2021) - Sun, Dewen; Ma, Yingjie; Lu, Liqun; Qi, Shuai; Hou, Pingping; Li, Bo; Ran, Qianping; Liu, Jiaping; Hong, Jinxiang
Abstract: The synthesis process of dopamine hydrochloride functionalized palygorskite (Pal) nanoparticles (Pal@PDA) is optimized by adjusting the mass ratio of them. The optimal preparation technology of the Pal@PDA is determined by scanning electron microscopy and comparing the adhesive strength between the biomimetic protective coatings and dry and water saturated concrete surface. When the mass ratio of dopamine hydrochloride to Pal is 1:4, the prepared Pal@PDA does not contain excess polydopamine (PDA) nanoparticles and the coatings incorporating the Pal@PDA have the highest adhesive strength on dry and water saturated concrete surface at the same conditions. Compared with the pure epoxy primer, the adhesive strength between the epoxy primer incorporating 5 wt% Pal@PDA and the water saturated concrete surface increases by 25.69% (from 3.282 to 4.125 MPa). Furthermore, the Pal@PDA is embedded into pure epoxy resin to prepare the biomimetic resin composites, the tensile strength and compressive strength of the composites incorporating 5 wt% Pal@PDA are 91.20% and 34.77% higher than that of pure epoxy resin, respectively. Further studies confirm that the active groups on the Pal@PDA surface form the stable covalent and non‐covalent bonds with epoxy primer and the water saturated concrete surface, which is the major mechanism of improving interfacial adhesion. Abstract : The preparation process of dopamine hydrochloride functionalized palygorskite nanoparticles (Pal@PDA) were optimized and the optimal Pal@PDA were embedd into the wet‐curing epoxy primer and epoxy resin, respectively. The active groups on the surface of Pal@PDA could form stable covalent and non covalent bonds with the epoxy primer and the wet or water saturated surface of concrete, thus effectively improving the interfacial bonding strength between them and the mechanical strength of the resin matrix itself.